The Association Between Metabolic Disturbance and Cognitive Impairments in Early-Stage Schizophrenia - Peng, Xing-Jie; Hei, Gang-Rui; Li, Ran-Ran; Yang, Ye; Liu, Chen-Chen; Xiao, Jing-Mei; Long, Yu-Jun; Shao, Ping; Huang, Jing; Zhao, Jing-Ping; Wu, Ren-Rong (Frontiers in Human Neuroscience, 2021)
Background: Cognitive impairment is one of the core symptoms of schizophrenia, which is considered to be significantly correlated to the prognosis. In recent years, many studies have suggested that metabolic disorders could be related to a higher risk of cognitive defects in general setting. However, there has been limited evidence on the association between metabolism and cognitive function in patients with early-stage schizophrenia. Methods: In this study, we recruited 172 patients with early-stage schizophrenia. Relevant metabolic parameters were examined and cognitive function were evaluated by using MATRICS Consensus Cognitive Battery (MCCB) to investigate the relationship between metabolic disorder and cognitive impairment. Results: Generally, the prevalence of cognitive impairment among the patients in our study was 84.7% (144/170), which was much higher than that in the general population. Compared with the general Chinese setting, the study population presented a higher proportion of metabolic disturbance. Patients who had metabolic disturbance showed no significant differences on cognitive function compared to other patients. Correlation analysis showed that metabolic status was significantly correlated with cognitive as assessed by the cognitive domains scores (p<0.05), while such association was not found in further multiple regression analysis. Conclusions: Therefore, there may be no association between metabolic disorder and cognitive impairment in patients with early-stage schizophrenia.